Continuous Hydrothermal Synthesis of Metal Germanates (M2GeO4; M = Co, Mn, Zn) for High‐Capacity Negative Electrodes in Li‐Ion Batteries. Issue 1 (22nd October 2019) - Bauer, Dustin; Ashton, Thomas E.; Groves, Alexandra R.; Dey, Avishek; Krishnamurthy, Satheesh; Matsumi, Noriyoshi; Darr, Jawwad A.
Abstract : Nanosized metal germanates ( M 2 GeO4 ; M  = Co, Mn, Zn) are synthesized using a continuous hydrothermal flow synthesis process for the first time. The electrochemical properties of all samples as active materials for negative electrodes in Li‐ion half cells are explored. The galvanostatic and potentiodynamic testing is conducted in the potential range of 3.00–0.05 V versus Li/Li + . The results suggest that both alloying and conversion reactions associated with Ge contribute to the stored charge capacity; Zn2 GeO4 shows a high specific capacity of 600 mAh g −1 (ten cycles at 0.1 A g −1 ) due to alloying and conversion reactions for both Ge and Zn. Mn2 GeO4 is studied for the first time as a potential negative electrode material in a Li‐ion half cell; an excellent specific charge capacity of 510 mAh g −1 (10 cycles per 0.1 A g −1 ) is obtained with a significant contribution to charge arising from the conversion reaction of Mn to MnO upon delithiation. In contrast, Co2 GeO4 only shows a specific capacity of 240 mAh g −1, after ten cycles at the same current rate, which suggests that cobalt has little or no benefit for enhancing stored charge in germanate. Abstract : Continuous hydrothermal flow synthesis of nanosized metal germanates ( M 2 GeO4 ; M  = Co, Mn, Zn) is conducted for the first time. These materials show both alloying and conversion reactions associated with Ge and impressive specific capacities of 600 mAh g −1 (Zn2 GeO4 ), 510 mAh g −1 (Mn2 GeO4 ), and 240 mAh g −1 (Co2 GeO4 ).